Bone Talk - Gourlay, Candy (New York : Scholastic, Inc., 2019)
"More than a hundred years ago, a boy named Samkad thinks he knows everything about the world. He knows the mountains he lives in. He knows his people. He knows his blood enemy, the Mangili. And he wants to become a man, to be given his own shield, spear and axe to fight with. His best friend, Luki, wants all the same things - but she is a girl, and no girl has ever become a warrior. But everything changes when a new boy arrives in the village. He calls himself Samkads brother, yet he knows nothing of the ways of the mountain. And he brings news of a people called Americans, who are bringing war and destruction right to his home..."--Publishers description.
Keywords: Boys -- Juvenile fiction; Villages -- Philippines; Juvenile fiction; Tribes -- Philippines; Juvenile fiction; Philippines -- History -- 1812-1898; Juvenile fiction; Philippines -- History -- Philippine American War, 1899-1902; Juvenile fiction